Comparative Study on Two Statistical Wave Load Models and Their Application to Fatigue Assessment - Gracia, Luis De; Wang, Helong; Mao, Wengang; Osawa, Naoki; Rychlik, Igor (2019)
The shipbuilding industry has been under constant development. Nowadays, bigger and lighter ships are sailing worldwide shipping routes, and one of the crucial structural problems to be challenged is the fatigue damage to the hull structure. Ships structures should be safe and reliable against different kinds of fractures e.g., brittle fracture, fatigue failure, buckling, plastic collapse, among others. The corrosion, welding defects, material properties, wave load computations, etc, generally include large uncertainties in the ship fatigue analysis. In particular, large uncertainties are associated with the difference of the provided from actual wave environments encountered by a ship. These uncertainties may lead to fatigue cracks initiated much earlier than expected. The wave scatter diagrams, generally provided by the class rules guidelines, indicate the long-term probability distribution of waves at a specific sea area. Therefore, the actual wave environment encountered by individual ships may be not consistent with that provided by the class rule guidelines that are unlikely to consider operational conditions for individual ships. Therefore, a reliable description of the wave environments encountered by the ship during her service life is essential for the accurate fatigue assessment of ship structures. Statistical wave load models have been developed to model wave environments along ship arbitrary routes based on diverse wave data, e.g., onboard observations, satellite measurements, buoy data, and reanalysis data, etc. The wave information generated by the wave models could be useful for ship fatigue assessment and extreme loading predictions. This study presents two statistical wave models, one is based on wave scatter data extracted from reanalysis dataset along ship routes and the other is based on the Spatio-temporal correlation of wave from reanalysis and satellite measurements. A series of full-scale measurement data collected in a 2800TEU container carrier, when sailing in the North Atlantic during ...